Penguatan Peran Masyarakat Desa sebagai Mitra Pemerintah melalui Pelatihan Perencanaan, Pelaksanaan dan Evaluasi Hasil Pembangunan Desa - Sri Yulianty Mozin; Romy Tantu (Univeristas Negeri Gorontalo, 2021)
Village development is a process that includes a series of activities including planning, implementing, and supervising village development. The community is mandated to participate actively. Therefore, the implementation of the Thematic Community Service Program to Build Village UNG in 2021 aims to achieve success at the community level and village government level. The method used is focused on mentoring efforts to strengthen community/village institutions in the village development process. The results of the service show an increase in the principle of participation in village development and the breadth of spaces for students to learn with the community about village development.